Limosilactobacillus reuteri DS0384 promotes intestinal epithelial maturation via the postbiotic effect in human intestinal organoids and infant mice. (31st December 2022) - Lee, Hana; Jung, Kwang Bo; Kwon, Ohman; Son, Ye Seul; Choi, Eunho; Yu, Won Dong; Son, Naeun; Jeon, Jun Hyoung; Jo, Hana; Yang, Haneol; Son, Yeong Rak; Yun, Chan-Seok; et al.
ABSTRACT: Little is known about the modulatory capacity of the microbiota in early intestinal development. We examined various intestinal models that respond to gut microbial metabolites based on human pluripotent stem cell-derived human intestinal organoids (hIOs): physiologically relevant in vitro fetal-like intestine, intestinal stem cell, and intestinal disease models. We found that a newly isolated Limosilactobacillus reuteri strain DS0384 accelerated maturation of the fetal intestine using 3D hIO with immature fetal characteristics. Comparative metabolomic profiling analysis revealed that the secreted metabolite N-carbamyl glutamic acid (NCG) is involved in the beneficial effect of DS0384 cell-free supernatants on the intestinal maturation of hIOs. Experiments in an intestinal stem cell spheroid model and hIO-based intestinal inflamed model revealed that the cell-free supernatant from DS0384 comprising NCG promoted intestinal stem cell proliferation and was important for intestinal protection against cytokine-induced intestinal epithelial injury. The probiotic properties of DS0384 were also evaluated, including acid and bile tolerance and ability to adhere to human intestinal cells. Seven-day oral administration of DS0384 and cell-free supernatant promoted the intestinal development of newborn mice. Moreover, NCG exerted a protective effect on experimental colitis in mice. These results suggest that DS0384 is a useful agent for probiotic applications and therapeutic treatment for disorders of early gut development and for preventing intestinal barrier dysfunction.